The Effect of Profitability and Company Size On Company Value With Dividend Policy As A Mediation Variable - Dewa Ayu Septia Ardianti; Henny Rahyuda (Dinasti Publisher, 2024)
Company value reflects the current state of the company and can describe the company's prospects in the future. High company value can increase market confidence in company performance. This research aims to analyze the influence of profitability and company size on company value with dividend policy as a mediating variable on the Indonesian Stock Exchange. The population in this research is all banking companies listed on the Indonesia Stock Exchange in the 2020-2022 period, namely 46 companies. The number of samples in this research was 14 companies listed on the Indonesia Stock Exchange using a non-probability sampling method with purposive sampling technique. Data was collected from the company's annual financial reports from 2020-2022. Data analysis was carried out using path analysis techniques. The results of this research show that profitability and dividend policy have a positive effect on company value, while company size has no effect on company value. Profitability and company size also have no effect on dividend policy. The research results also show that dividend policy is unable to mediate the influence of profitability and company size on company value.